Evaluasi Risiko Gangguan Musculoskeletal Disorders pada Pekerja Industri Rumah Tangga Kerupuk Kulit Menggunakan Metode Rula - Safitriyawi, Roja; Lestari, Suci Ayu; Ulfah, Tya (Jurnal Optimalisasi, 2025)
One of the most prominent types of home industries operated by local entrepreneurs is the food processing sector, particularly the production of skin crackers.  However, the production process remains predominantly manual, with workers performing each stage such as cutting, drying, frying, and packaging either individually or in groups. Such manual operations inherently expose workers, especially older individuals, to ergonomic risks. Many workers have reported experiencing musculoskeletal discomfort, including rheumatic pain and muscle stiffness, due to prolonged and repetitive tasks. This study aims to analyze workers’ upper body postures to identify potential musculoskeletal disorders (MSDs) using the Nordic Body Map (NBM) Questionnaire and to evaluate work postures using the Rapid Upper Limb Assessment (RULA) method. Data were collected through structured interviews and direct field observations in the skin cracker home industry. The results indicate a RULA score of 7 for all key production processes cutting, drying, frying, and packaging, corresponding to Action Level 4, which signifies that immediate investigation and corrective action are required. The recommended measures include implementing regular stretching or exercise between work activities, redesigning workstations and tools based on workers’ anthropometric data and task requirements, regulating working hours to not exceed eight hours per day, and conducting periodic layout reorganization and workplace maintenance to enhance safety and productivity.